Strategi Pemberdayaan Perusahaan Waralaba Lokal Menuju Waralaba Global: Studi Kasus Good Corporate Governance oleh Eksekutif Puncak di J.Co, Es Teller 77, dan Pecel Lele Lela - Lelo Yosep Laurentius (Bina Nusantara University, 2015)
This research is mainly intended for reviewing and strengthening leadership, corporate governance good practices and management philosophy in the concepts, systems, and human resources (HR) of the company. A new progressive corporate leader should be able to quickly identify the strengths and weaknesses of his/her business, to increase the first and to reduce the pressures or to liquidate the later. Finally, he/she must be able to encourage his/her subordinates to achieve easily identified and highly attractive goals. The target is to build the 21st century company where all employees realize that they can make it different and that they will warmly welcome the managerial motivation. Thus, the chief executive officer assumes the responsibility for constructive managerial skills. Research used qualitative approach to disclose GCG in local franchise companies. Case study was done purposively with chief executive officer of the company. Data were gathered by observation and literature study. Analysis was conducted by data reduction, data presentation, and conclusion.